Physicochemical analysis of floral honeys produced by Apis mellifera L. between 2018 and 2020 in the State of Santa Catarina, southern Brazil - Nunes, Aline; Azambuja, Giovanna Balen de; Deolindo, Guilherme Luiz; Rita, Cleiciane; Azevedo, Gadiel Zilto; Santos, Beatriz Rocha dos; Araújo, Denise Nunes; Moura, Sidnei; Maraschin, Marcelo (Revista de Ciências Agroveterinárias, 2024)
Brazil is a major producer of honey and is internationally recognized for the quality of this product. To assess the quality of the product, physicochemical analyses were carried out. In this sense, samples of honey from the eleven agroecological zones of Santa Catarina, southern Brazil, were analyzed for moisture content, pH, reducing sugars, apparent sucrose, water activity, diastase enzyme, color, and Lund reaction. Sixty-five samples of honey collected in the 2018-2019 harvest and 50 in the 2019-2020 harvest were analyzed. The data were analyzed using analysis of variance and the Scott & Knott test (p<0.05) with the aid of scripts written in the R language. Principal component analysis (PCA) was also applied to the physicochemical dataset to verify possible sample groupings between the agroecological zones of the State and interactions between the variables. Moisture and apparent sucrose contents of the honey showed the greatest discrepancies in their values regarding what is permitted by the Brazilian legislation. Three agroecological zones were correlated in terms of the data found. PCA showed that moisture, pH, and water activity were relevant physicochemical parameters for grouping and discriminating samples. From the results herein shown, it is perceived the need for continuous monitoring of honey produced in Santa Catarina State, as well as the qualification of beekeepers for harvesting, processing, and storage.